2019
DOI: 10.1002/eco.2073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of river damming on ground‐dwelling arthropods along riparian–upland habitats

Abstract: River damming is one of the most serious anthropogenic disturbances impacting river ecosystems. Little is known about the consequences of river damming on grounddwelling arthropods, although they represent a functionally important component of riverine ecosystems because they provide an essential link between aquatic and terrestrial ecosystems. We investigated the effects of river damming on the composition and structure of arthropod communities in the Baijia Stream located in the centre of the Three Gorges Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Since the start of formal operation of the Three Gorges Reservoir, the annual water level regulation has led to fluctuations in water levels in the area in front of the dam, ranging from 145 m to 175 m [24]. The riparian zone with water level fluctuation in the Three Gorges Reservoir area of the Yangtze River is a periodically flooded area that forms on both sides of the river channel due to controlled variations in water levels.…”
Section: Area Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the start of formal operation of the Three Gorges Reservoir, the annual water level regulation has led to fluctuations in water levels in the area in front of the dam, ranging from 145 m to 175 m [24]. The riparian zone with water level fluctuation in the Three Gorges Reservoir area of the Yangtze River is a periodically flooded area that forms on both sides of the river channel due to controlled variations in water levels.…”
Section: Area Descriptionmentioning
confidence: 99%
“…At the cross section of the riparian zone, there are three distinct elevation ranges: the section between 145 and 155 m is frequently submerged, the section between 155 and 165 m experiences approximately i6 months of inundation and 6 months of exposure, and the section between 165 and 175 m is often exposed. Consequently, based on these fluctuations in water level, the riparian zone was categorized into three sample zones: 145 to 155 m denoted as the regular water-flooded zone (Zone A); 155 to 165 m as the semi-flooded and semi-exposed zone (Zone B); and 165 to 175 m as the regularly exposed zone (Zone C) [24].…”
Section: Surveymentioning
confidence: 99%
“…Terrestrial beetle communities can reflect variability in environmental factors such as sediment and vegetation Ramey & Richardson, 2017;Sadler et al, 2004), hydromorphology (Paetzold et al, 2008;Sinnadurai et al, 2016;Wang et al, 2019), land use (Edwards & Huryn, 1996;Stenroth et al, 2015) and management interventions (Januschke & Verdonschot, 2016), and are thus useful for biomonitoring in riparian habitats (Rainio & Niemelä, 2003). To enable the response of terrestrial beetles to habitat conditions to support evidence-informed decision making in the UK, Eyre and Lott (1997) recommended development of a standardized field survey protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of benthic and aquatic arthropods have shown that reservoir construction and other forms of hydrological alteration can lead to declines in arthropod abundance and/or diversity and modify arthropod community composition across short and long time‐scales, with environmental variables such as water temperature and nutrient levels often mediating these effects (Carlisle et al, 2016; Romero et al, 2021). Riparian (or partially riparian) arthropods, including insects, can be similarly negatively affected by anthropogenic changes in hydrology, such as flow management (Jonsson et al, 2013; Paetzold et al, 2008; Wang et al, 2019), but this is not always the case (Ellis et al, 2001), and the small number of past studies precludes generalisation. Moreover, the hydrological disruption associated with the TGD has occurred on an unprecedented spatial scale, such that its consequences for riparian insects, and riparian ecosystems generally, may differ distinctly from consequences observed in prior studies.…”
Section: Introductionmentioning
confidence: 99%